SUBSTRATES FORMULATED WITH ORGANIC RESIDUES IN THE PRODUCTION OF SEEDLINGS OF Moquiniastrum polymorphum - Faria, Julio Cezar Tannure; de Melo, Lucas Amaral; Brondani, Gilvano Ebling; Delarmelina, William Macedo; da Silva, Diana Suzete Nunes; Nieri, Erick Martins (Floresta, 2017)
The composition of the substrate utilized as a growth medium is directly related to the seedling quality, being important the conduction of studies seeking an increased understanding of its formulation for seedling production. The objective of this study was to check the potential of the biosolid, cattle manure and coconut fiber in the evaluation of different substrate formulations for the production of seedlings of the forest species Moquiniastrum polymorphum. The experiment was conducted in structures of a forest nursery, localized in the municipality of Lavras-MG, in 110 cm³ tubes arranged in a completely randomized design constituted by five treatments with four replications of 54 seedlings per plot. When the seedlings reached 150 days after sowing, plant height, collet diameter, height/diameter ratio, shoot dry mass, root system dry mass, total dry mass and the shoot/root dry mass were measured, in addition to the Dickson Quality Index - DQI. It was found by means of the results obtained that for the production of seedlings of M. polymorphum, the use of substrates formulated from 20 to 60% of biosolid + 20 to 60% of cattle manure + 20% of coconut fiber is recommended. Key words: Biosolid; Gochnatia polymorpha; Seedling quality; Silviculture; Forest nursery. Resumo Formulação de substrato com resíduos orgânicos na produção de mudas de Moquiniastrum polymorphum. A composição do substrato utilizado como meio de crescimento está diretamente relacionada com a qualidade de mudas, sendo importante a realização de estudos que busquem uma maior compreensão de sua formulação para produção de mudas. O objetivo deste estudo foi verificar o potencial do uso do biossólido, esterco bovino e fibra de coco na avaliação de diferentes formulações de substratos para a produção de mudas da espécie florestal Moquiniastrum polymorphum. O experimento foi conduzido no Viveiro Florestal da Universidade Federal de Lavras (UFLA), em tubetes de 110 cm³, sendo instalado em um delineamento inteiramente casualizado constituído por cinco tratamentos, com quatro repetições de 54 mudas por parcela. Quando as mudas atingiram 150 dias após a semeadura, foram mensurados a altura das plantas, o diâmetro do coleto, a relação altura/diâmetro, a massa seca da parte aérea, a massa seca do sistema radicular, a massa seca total e a relação massa seca da parte aérea/raiz, além do índice de qualidade de Dickson (IQD). Por meio dos resultados obtidos, constatou-se que para a produção de mudas de M. polymorphum recomenda-se o uso de substratos formulados a partir de 20 a 60% de biossólido + 20 a 60% de esterco bovino + 20% de fibra de coco. Palavras-chave: Biossólido; Gochnatia polymorpha; qualidade de mudas; Silvicultura; Viveiro florestal.